The ameliorative effects of melatonin against BDE-47-induced hippocampal neuronal ferroptosis and cognitive dysfunction through Nrf2-Chaperone-mediated autophagy of ACSL4 degradation - Quan Yuan; Mingwei Wang; Zhaoxiang Zhang; Ruofei Wang; Dechao Wang; Zichun Sang; Pu Zhao; Xiaoli Liu; Xiaoying Zhu; Gaofeng Liang; Hua Fan; Dongmei Wang (Ecotoxicology and Environmental Safety)
Recent studies demonstrate that lipid peroxidation-induced ferroptosis participates in 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47)-evoked neurotoxicity and cognitive dysfunction. Melatonin has been indicated to confer neuroprotection against brain diseases via its potent anti-ferroptotic effects. Therefore, this study aims to explore whether melatonin can mitigate BDE-47-elicited cognitive impairment via suppressing ferroptosis, and further delineate the underlying mechanisms. Our results found that melatonin administration effectively inhibited BDE-47-induced ferroptosis in mice hippocampi and murine hippocampal neuronal HT-22 cells. Acyl-CoA synthetase long-chain family member 4 (ACSL4), a key lipid metabolism enzyme dictating ferroptosis sensitivity, accompanied by higher MDA and lipid reactive oxygen species (ROS), was remarkably increased under BDE-47 stress, while melatonin supplementation could suppress the elevated ACSL4 in vivo and in vitro. Furthermore, melatonin facilitated lysosomal ACSL4 degradation through enhancing lysosome-associated membrane protein type 2a (LAMP2a) expression and chaperone-mediated autophagy (CMA) activity, while LAMP2a knockdown abrogated the positive effects of melatonin on ACSL4 elimination in BDE-47-treated HT-22 cells. Moreover, nuclear factor erythroid 2-related factor 2 (Nrf2) activation by melatonin contributed to LAMP2a upregulation and CMA of ACSL4 and subsequent neuronal ferroptosis. Importantly, melatonin, CMA activator CA77.1, and ACSL4 inhibitor rosiglitazone (RSG) administration substantially attenuated neuronal/synaptic injury and cognitive deficits following BDE-47 exposure. Taken together, these findings revealed that melatonin could prevent BDE-47-provoked ferroptosis in the hippocampal neurons and mitigate cognitive dysfunction by facilitating ACSL4 degradation via Nrf2-chaperone-mediated autophagy. Therefore, melatonin might be a potential candidate for treating BDE-47-elicited neurotoxicity and neurobehavioral disorder.